2013
DOI: 10.1042/bj20121750
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics of collagen receptor networks reveals SHP-2 phosphorylation downstream of wild-type DDR2 and its lung cancer mutants

Abstract: Collagen is an important extracellular matrix component that directs many fundamental cellular processes including differentiation, proliferation and motility. The signalling networks driving these processes are propagated by collagen receptors such as the β1 integrins and the DDRs (discoidin domain receptors). To gain an insight into the molecular mechanisms of collagen receptor signalling, we have performed a quantitative analysis of the phosphorylation networks downstream of collagen activation of integrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 56 publications
(80 reference statements)
9
63
0
Order By: Relevance
“…49,50). While the precise mechanism or mechanisms underlying dasatinib sensitivity are beyond the scope of this report, the general mechanisms and consequences of discoidin domain receptor signaling in cancer are areas of ongoing research (47)(48)(49)(50)56). The DDR2(R709*) mutation identified in the metachronous recurrent tumor of patient PY-3, which conferred the greatest degree of sensitization to dasatinib in the present study, has also been reported in gastric and endometrial cancers.…”
Section: Discussionmentioning
confidence: 75%
“…49,50). While the precise mechanism or mechanisms underlying dasatinib sensitivity are beyond the scope of this report, the general mechanisms and consequences of discoidin domain receptor signaling in cancer are areas of ongoing research (47)(48)(49)(50)56). The DDR2(R709*) mutation identified in the metachronous recurrent tumor of patient PY-3, which conferred the greatest degree of sensitization to dasatinib in the present study, has also been reported in gastric and endometrial cancers.…”
Section: Discussionmentioning
confidence: 75%
“…However, the study did not address the contribution of wild-type DDR2 to oncogenesis, and while several more recent studies have confirmed the occurrence of DDR2 mutations in different patient populations [122][123][124], it is far from clear whether the mutations are indeed oncogenic and their roles in lung SCC cell signalling are undefined [125]. Notably, in other studies, some of the 'oncogenic' DDR2 mutants either seemed to play tumour suppressive functions [101], or did not contribute to cell proliferation in lung SCC cell lines [126].…”
Section: Ddrs and Cancermentioning
confidence: 98%
“…Other molecules known to interact with phosphorylated DDR1 include the phosphatases SHP-1 [98] and SHP-2 [97,99] and members of the Stat family of transcription activators [99,100]. For DDR2, downstream effectors include SHP-2, Nck1, the Src family kinase Lyn and phospholipase C-like 2 [101], but it is not known whether any of these interact directly with the activated receptor.…”
Section: Ddr Signallingmentioning
confidence: 99%
“…The loss of DDR2 has also been shown to predispose hepatic tissues to colon carcinoma cell growth and metastasis (29). Moreover, wild-type DDR2 expression in the HEK293 cell line greatly reduced colony formation in the presence of collagen (30). Collagen is the major structural component of the extracellular matrix and triggers many intercellular signal pathways regulating cellular growth, migration, and differentiation (31).…”
Section: Discussionmentioning
confidence: 99%